Constructivism and the Pedagogy of Education for Peace: A Reflection on School Education Curriculum Reform (NCF–2005) - Pandey, Saroj (JOURNAL OF INDIAN EDUCATION, 2007)
This paper has been developed against the backdrop of National Curriculum Framework – 2005, which envisages major paradigm shift from behaviourist approach to learning to constructivist approach that lays stress on the personal experiences of learner in the process of knowledge construction. The role of teacher in this approach has shifted from the transmitter of knowledge to facilitator of knowledge. The NCF – 2005 also emphasises on education for peace, not as a part of value education as traditionally been integrated in schools, but, as an independent value in itself. The paper highlights the implication of this paradigm shift in the approach towards learning for promoting the culture of peace as, both, the constructivist approach and peace education are associated with the humanistic philosophy which is dedicated to developing more mature and self-directed learner – a pre-requisite for living together. To develop a culture of peace, the pedagogy of education needs to be broad, diverse and oriented towards lifelong learning. Active listening, problem-solving, and conflict resolution skills help in inculcating feeling of living together, which are also basic to the constructivist way to learning. Therefore, the epistimological shift suggested in the NCF – 2005 provides greater opportunity to promote the culture of peace than ever before.